ISLAM DALAM TRADISI ERAU DI KALIMANTAN TIMUR: IMPLIKASINYA TERHADAP EKOTEOLOGI MASYARAKAT - Abdul Rahmat; Mursalim Juniad; Khairuddin Kiramang (FISIP Universitas Malikussaleh, 2026)
This study examines the relationship between Islam, local cultural traditions, and ecotheological practices in community life, particularly in the context of efforts to preserve the environment. Human interaction with nature is inherently integral to meeting life's needs, but these practices often unwittingly damage ecosystems, such as tree felling, which causes floods and landslides. Nevertheless, some communities still uphold local wisdom values as a strategy for environmental preservation. The local Islamic perspective also provides a strong theological foundation for the importance of maintaining the balance of nature, reflected in the teachings of amanah (trust), the prohibition of destruction (fasad), and the obligation to provide benefits for all creatures. Through an integrative approach between Islamic teachings and local traditions, communities have developed an ecotheological model grounded not only in spiritual dimensions but also in socio-cultural practices such as forest protection, natural resource conservation, and the strengthening of ecological ethics. This study demonstrates that the combination of Islamic values and local wisdom has significant implications for shaping community ecological behavior and opens up significant opportunities for strengthening faith-based ecotheology in addressing modern environmental challenges.